2003
DOI: 10.1093/ps/82.5.831
|View full text |Cite
|
Sign up to set email alerts
|

Long-term supplementation of various dietary lipids alters bone mineral content, mechanical properties and histological characteristics of Japanese quail

Abstract: The purpose of this study was to investigate the effects of long-term supplementation of fat in the diets on the fatty acid composition, chemical, mechanical, and histological properties of tibial bone. Month-old male Japanese quail were fed a basal diet containing either soybean oil (SBO), hydrogenated soybean oil (HSBO), chicken fat (CF), or menhaden fish oil (FO) at 50 g/kg of the diet and maintained on these diets for 7 mo. Lipid treatments did not affect body weight, food intake, tibial length, or diamete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
62
2
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(73 citation statements)
references
References 34 publications
5
62
2
2
Order By: Relevance
“…A study by Johnston et al (2006) demonstrated similar findings in turkeys. However, in young birds, several studies have shown that dietary n-3PUFA has a positive effect on the development, growth and modeling of long bones in growing chicks (Watkins et al, 1997) and growing Japanese quail (Liu et al, 2003), which have a direct and important role in facilitating the mineralization of bone tissues and strength of bone (Liu et al 2003). Also, it is well established that dietary lipids can modulate the fatty acid profile in cartilage and bone tissues (Watkins et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A study by Johnston et al (2006) demonstrated similar findings in turkeys. However, in young birds, several studies have shown that dietary n-3PUFA has a positive effect on the development, growth and modeling of long bones in growing chicks (Watkins et al, 1997) and growing Japanese quail (Liu et al, 2003), which have a direct and important role in facilitating the mineralization of bone tissues and strength of bone (Liu et al 2003). Also, it is well established that dietary lipids can modulate the fatty acid profile in cartilage and bone tissues (Watkins et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Following bone breaking, the bone wall thickness was measured at the midpoint mark using the micrometer. To determine tibial ash content, bones were oven-dried at 1058C for 24 h and ashed in a muffle furnace at 6008C for 14 h following the procedure of Liu et al (2003). The percentage ash was determined relative to the dry weight of the tibia.…”
Section: Humoral Immunitymentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous animal studies have shown a positive effect of n-3 PUFA on bone mineral density, bone mineral content and bone strength. Liu et al (2003) found out significantly higher bone mineral density and bone strength in quails fed a FOsupplemented diet (high in n-3 PUFA) compared to a soybean oil diet group (high in n-6 PUFA).…”
mentioning
confidence: 86%